Iniciação científica com projetos de botânica no Ensino médio - Silva, Tácia Michelle dos Santos (2019)
Scientific Initiation (SI) is the process in which is provided to student a set of techniques and norms peculiar to Science. In this sense, the actions are systematic, because it is desired the formation of research skills, as well as the introduction of new knowledge. The production of research projects, idealized and developed by the students, can be one of the means of working the Scientific Initiation in High School. In this context, the principles of the Active Methodology are used, since students assume the central role in the process and current as active and reflexive agents in the production of knowledge. In Biology, Botany has its value recognized, being essential for the survival of living beings, however, several texts highlight the difficulty in the teaching and learning process of this area of Science, using different arguments to explain this difficulty, non-specific teacher training, the complexity of the contents, the decontextualization with the everyday, the nomenclature, among others, that generate little or no interest on the part of the students. In view of the above, the main objective of the work was to use scientific research, through the development of projects designed and carried out by high school students, as a means of approaching issues related to Botany, in order to meet the requirements of the Active Methodology. The research was developed in a state school of integral and vocational education, in the city of Teotônio Vilela (AL), with students of the three years of High School, of the different genres. Five projects were developed at the end of the project: Carpoteca, Medicinal and toxic plants, Suspended vegetable garden, Ornamental plants and a Blog. There was a marked improvement in the level of student interest in the study object and in content directly related to botany. Throughout the process students worked with research, so they were inserted daily in the SI, developing skills such as protagonism, leadership, autonomy, collaboration, cooperation, teamwork, problem solving, time management, among others. In this way, it is believed that this is a methodology that can be used quite efficiently, especially when the goal is greater development of different skills in the individual and not a specific content of the discipline. It is important to highlight the challenges of the workload, the decentralization of the teacher figure and the dynamics of the school and its pedagogical coordination.